The Optimization of Hybrid Air Ventilation System Combined with Silica Gel and Thermoelectric Using Monitoring Control - Jirod Chaisan; Somchai Maneewan; Chantana Punlek (Institute of Advanced Engineering and Science, 2018)
In this paper, the experimental is evaluated temperature, humidity and air pollution from CO2 by monitoring control of hybrid air ventilation for producing fresh air. The experimental divided into 2 conditions: hybrid air ventilation on-off, recovery silica gel unit. That research consider of a voltage of thermoelectric devices relative with air cooling under thermal comfort zone Thailand climate conditions. In the experimental was designed by the DOAS system (dedicate outdoor air system) concept. Whereas, the hybrid air ventilation was improved by old air ventilation which the hybrid air ventilation combined with silica gel unit and thermoelectric device. Monitoring control is written by Arduino program that is open source for control performance of processes such as sensors, electric current and fan unit. That working is specified temperature and humidity Thailand thermal comfort range. In the part of CO2 was released rate approximately 900 ppm corresponded with indoor air quality standard (IAQs). The results of experimental suggested that in case of hybrid air ventilation system explained thermal, humidity and CO2 distribution due to the system was adapted significantly in the comfort zone temperature and humidity about 28 and 58% respectively. However, the CO2 released into the hybrid air ventilation although control during 900 – 1,000 ppm. High CO2 concentration in comfort zone used the hybrid air ventilation that decreased CO2 inlet under ASHRAE 62.2. Therefore, the experimental is an evaluation of monitoring control hybrid air ventilation for management comfort zone. Finally this research concept of the optimization of the hybrid air ventilation combination with thermoelectric devices and silica gel unit.